Analysis of Scheduling Performance and Stability in Wireless Ad-Hoc Networks Using ACO, MWS and Novel ACO-MWS - Sindhupiriyaa, B; Maruthanayagam, D (International Journal of Computer Sciences and Engineering, 2025)
Multi-hop wireless networks and Routing management, it has is a vital and challenging resource allocation technique in Scheduling process. A distributed low-complexity scheduling algorithm develops into more challenging tasks, even if taking into account a physical interference model. At previous years a number of scheduling algorithms were presented, but pre-existing scheduling algorithm does not solve the drawbacks to implement in multi hop networks to overcome these issues, proposed a new scheduling approach Ant Colony Optimization Max-Weight Scheduling (ACO-MWS) for scheduling and routing in multi-hop wireless networks. The combination of proposed approaches such as ACO Algorithm and Max-Weight Scheduling that overcome the pre-existing scheduling problems and it accomplish maximum throughput at the distributed low complexity. The performance evolution of ACO, Max-Weight, and ACOMWS are presented in this paper.